2002
DOI: 10.1016/s1097-2765(02)00734-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Drosophila MLK by Ceramide Reveals TNF-α and Ceramide as Agonists of Mammalian MLK3

Abstract: Mixed lineage kinases (MLKs) are MAPKKK members that activate JNK and reportedly lead to cell death. However, the agonist(s) that regulate MLK activity remain unknown. Here, we demonstrate ceramide as the activator of Drosophila MLK (dMLK) and identify ceramide and TNF-alpha as agonists of mammalian MLK3. dMLK and MLK3 are activated by a ceramide analog and bacterial sphingomyelinase in vivo, whereas a low nanomolar concentration of natural ceramide activates them in vitro. Specific inhibition of dMLK and MLK3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
92
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 21 publications
9
92
1
1
Order By: Relevance
“…The antibodies used were obtained from the following sources: actin from Sigma, PPAR␥ from Santa Cruz Biotechnology (Santa Cruz, CA), E-cadherin and total GSK3␤ from BD Transduction Laboratories (Franklin Lakes, NJ), Phospho-␤-catenin (Ser 33/37 /Thr 41 ) and Phospho-GSK3␤ (Ser 9 ) from Cell Signaling Technology (Beverly, MA), HA.11 from BabCO (Richmond, CA), ␤-catenin from Zymed Laboratories (San Francisco, CA), APC from Oncogene (San Diego, CA), and 9E10 as described earlier (45). HA-tagged-wildtype-␤-catenin or S37A-␤-catenin constructs were obtained from Dr.…”
Section: Methodsmentioning
confidence: 99%
“…The antibodies used were obtained from the following sources: actin from Sigma, PPAR␥ from Santa Cruz Biotechnology (Santa Cruz, CA), E-cadherin and total GSK3␤ from BD Transduction Laboratories (Franklin Lakes, NJ), Phospho-␤-catenin (Ser 33/37 /Thr 41 ) and Phospho-GSK3␤ (Ser 9 ) from Cell Signaling Technology (Beverly, MA), HA.11 from BabCO (Richmond, CA), ␤-catenin from Zymed Laboratories (San Francisco, CA), APC from Oncogene (San Diego, CA), and 9E10 as described earlier (45). HA-tagged-wildtype-␤-catenin or S37A-␤-catenin constructs were obtained from Dr.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown that TNF-␣ also induces MLK3 activity in Jurkat T Cells (22) and that TNF-␣-induced cell death was inhibited by CEP-11004, a specific mixed lineage kinase inhibitor in PC-12 cells (21). These observations along with our Immunoblotting with anti-GST antibody was done to check the expression of various constructs used in the assay.…”
Section: Fig 2 Endogenous and Recombinant Mlk3 Interact With Akt Anmentioning
confidence: 99%
“…MLK3-induced JNK activation is implicated in apoptosis of neuronal cells in response to trophic factor withdrawal (4 -7). MLK3 also activates JNK in Jurkat T lymphocytes (8) and MCF-7 breast cancer cells (9) in response to tumor necrosis factor ␣ treatment. MLK3 activates the p38 pathway through phosphorylation of MKK3/6 (10), although this activity may be dependent upon the scaffold JIP2 (11,12).…”
mentioning
confidence: 99%